Negotiating Between Shell And Paper: Wampum Belts As Agents Of Religious Diplomacy - Puyo, Lise (2022)
In a dialogue between the material and the textual, can objects speak over texts? This project examines nine devotional wampum belts produced as cross-cultural mediators between Catholic ecclesiastics and Indigenous people in northeastern North America between the seventeenth and nineteenth centuries. Following Haudenosaunee, Huron-Wendat, Abenaki, and Anishinaabe epistemologies, wampum belts have been considered as both symbols of Native American and First Nations sovereignty, and as non-human beings doted with agency and willpower. When Indigenous Christians sent wampum belts to religious communities in France, Belgium, and Italy, these objects embodied diplomatic requests presented to Christian saints worshipped at these sites. Did these wampum belts function as independent diplomatic agents, without the presence of Indigenous interpreters? If so, what were these belts meant to do? I suggest that there may be heretofore unexamined messages, embedded in the material and documentary record, that reveal the agency and potency of these objects. Closer engagements with wampum materiality can offer insights that are missing from earlier historical studies of missionary-Indigenous relations. To discern this, I examined construction techniques that may reveal Indigenous makers’ agency in articulating political demands. I conducted archival research and re-examined historical translations, while consulting with the Indigenous communities in Canada who created these wampum belts, to assess how wampum messaging impacts the consciousness of humans around it. These diverse sources illuminate the transfers of agency that take place during wampum diplomacy, showing the embodied innovations and continuities that allowed these materials to “speak” across space and time. These wampum belts constitute an alternative archive of both Indigenous and missionary strategies. The objects and associated papers show savvy Indigenization of Catholic stories and practices to secure new alliances and territories, at the same time that ...